Nuclear effects on the transverse momentum spectra of charged particles in pPb collisions at [Formula: see text] [Formula: see text] - Khachatryan, V. (Eur Phys J C Part Fields, 2015)
Transverse momentum spectra of charged particles are measured by the CMS experiment at the CERN LHC in pPb collisions at [Formula: see text] [Formula: see text] , in the range [Formula: see text] [Formula: see text] and pseudorapidity [Formula: see text] in the proton–nucleon center-of-mass frame. For [Formula: see text] [Formula: see text] , the charged-particle production is asymmetric about [Formula: see text] , with smaller yield observed in the direction of the proton beam, qualitatively consistent with expectations from shadowing in nuclear parton distribution functions (nPDF). A pp reference spectrum at [Formula: see text] [Formula: see text] is obtained by interpolation from previous measurements at higher and lower center-of-mass energies. The [Formula: see text] distribution measured in pPb collisions shows an enhancement of charged particles with [Formula: see text] [Formula: see text] compared to expectations from the pp reference. The enhancement is larger than predicted by perturbative quantum chromodynamics calculations that include antishadowing modifications of nPDFs.